(untitled) (Scientific journal of the Fergana State University, 2024)
Students with developed logical thinking have the opportunity to study at the highest level of education. The possibilities for developing students’ thinking in developed countries are analyzed. However, even in our country there are many difficulties in working with students who have developed logical thinking. The analysis showed that the teacher not only develops knowledge, skills and abilities in students, but also develops their leadership qualities and develops social cooperation skills.Thinking is a component of human mental activity, a mental stage of cognition that determines the common, important features of things and events in the world, reflects internal, necessary connections between them, that is, legal connections. Thinking has a number of characteristics according to its content and essence: reflecting reality in a general way; indirect expression of existence; to show that a person’s thinking has a creative character; such as the manifestation of thinking in an integral connection with the mother tongue.